Utilization of Digital Technology in Islamic Boarding Schools: A Case Study in Samarinda - Wijaya, Ida Suryani; Ridho, Miftahur; Hidayati, Diajeng Laily; Mahdi, Mahkamah (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
Pondok Pesantren (traditional Islamic boarding school) is one of Indonesia's most crucial pillars supporting educational needs. As the foremost institution upholding Islamic traditions in the archipelago, pesantren is expected to remain relevant amidst the advancements of the era without forsaking its deeply rooted values and traditions. Thus, this article aims to highlight the issue of technology utilization by pondok pesantren by describing the general landscape of digital media usage in several pesantren located in the Samarinda Seberang region, as well as analyzing the perceptions of pesantren administrators regarding the utilization of digital media as a means of information dissemination and as a tool to improve the overall management of pondok pesantren institution. To undertake this research, a phenomenological approach is employed to analyze data collected through observations, interviews, questionnaires, and documentation in six pondok pesantren in the Samarinda Seberang area. The findings reveal that the pondok pesantren in Samarinda Seberang are already familiar with the application of digital technology. However, this utilization remains limited to media based on images and videos. The incorporation of text-based technology is still restricted due to the lack of resources available to the pesantren.